Sustainable Curriculum Development Based on Contemporary Needs to Improve the Quality of Basic Education - Romi Laspita; Nurul Islami; Nor Aisya; Nur Syakila Mulya; Putri Amalia Peza; Saskia Mawaddah; Septi Valny Syahara; Widya Meliana; Widya Zahirah; Zakia Tri Wulandari; Rahma Aulia (The Future of Education Journal, 2026)
Curriculum development is a crucial aspect of improving the quality of basic education amid the rapid advancement of science, technology, and societal changes. A sustainable and adaptive curriculum is needed to ensure that the educational process can produce students with competencies that meet the demands of the 21st century. This article aims to examine the importance of sustainable curriculum development based on contemporary needs in improving the quality of primary education. The method employed in this study is library research by analyzing various relevant literature and research findings related to curriculum development, the implementation of the Merdeka Curriculum, 21st-century skills, and strategies for enhancing the quality of primary education. The findings indicate that sustainable curriculum development should consider students' needs, technological advancements, socio-cultural changes, and future workforce demands. An adaptive curriculum can promote more effective learning processes and enhance students' critical thinking, creativity, collaboration, communication, and digital literacy skills. Furthermore, the success of curriculum development requires support from various stakeholders, including the government, schools, teachers, and the community. Therefore, sustainable curriculum development based on contemporary needs is an essential strategy for creating high-quality, relevant primary education capable of preparing future generations to face global challenges.